Pengembangan Modul Ajar Mata Pelajaran Sosiologi Kelas XI Berbasis Four-D - Suyuti Suyuti; Devi Septiandini; Ike Arriany; Meilien Mocharom; Putri Wantini (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
This study aims to develop a sociology teaching module for eleventh-grade high school students using the Four-D model (Define, Design, Develop, Disseminate). The research employed a Research and Development (R&D) approach with the Four-D framework to address the challenges of teacher-centered learning and students’ lack of active engagement in sociology classes. The Define stage identified the need for innovative teaching resources due to the limitations of conventional methods. In the Design stage, a prototype module was created, integrating structured content, contextual examples, and student-centered activities. The Develop stage involved expert validation and limited trials, resulting in a module that achieved an average validity score of 4.2 (very valid) and practicality of 85% (very practical) according to student and teacher responses. The Disseminate stage demonstrated positive reception from teachers who confirmed the module’s usability in broader classroom contexts. Furthermore, effectiveness testing revealed a significant improvement in student learning outcomes, with an average pre-test score of 62.15 increasing to 82.35 in the post-test. The N-Gain score of 0.52 (moderate) and t-test results (p < 0.05) confirmed the module’s effectiveness. These findings suggest that the Four-D-based sociology teaching module is valid, practical, and effective, offering a relevant solution for enhancing critical thinking, independent learning, and contextual understanding of sociology concepts. This research contributes theoretically by expanding the application of the Four-D model in social science education and practically by providing a ready-to-use module for teachers and students in senior high schools.